An Evaluation of Organisational and Legal Forms in the Public Finance Sector in Quasi-market Conditions - Kosek-Wojnar, Maria; Maj-Waśniowska, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article looks at organisational and legal forms in the public finance sector. Bearing in mind the diverse rules of their creation and financing of public tasks, the main goal of the work was to analyse the principles of functioning of forms of financing public tasks operating under quasi-market conditions. The structure of the study reflects its specific objectives. It includes theoretical considerations regarding the criteria for choosing the organisational and legal form of financing public tasks and the legal basis for the functioning of executive agencies and budgetary authorities. In the empirical part of the work, the financial results of the forms discussed were analysed for the years 2011–2016 against the background of legal regulations. For methodology, the study uses comparative descriptive analysis. The research led to conclusions and observations that provide the basis for assessing the effectiveness of the forms of financing in the light of the financial results achieved, as well as for identifying discrepancies between statutory regulations and how they function.